Pendampingan Pemgembangan Usaha Potato Balls Di Kelurahan Ariang, Tana Toraja - Althon K Pongtuluran; Chandrawan Saranga; Martina Meti (GEMILANG: Jurnal Manajemen dan Akuntansi, 2021)
Through careful market research and monitoring of consumption trends, we see great potential in bringing new variations of the widely known potato dish. We believe that by combining delicious potatoes with a variety of interesting herbs and fillings, we can create something unique and appetizing.